Relationships : the heart of teaching? : a thesis presented in partial fulfillment of the requirements for the degree of Master of Education (Adult Education) at Massey University - Monk, Hilary (Massey University, 2004)
Learning and teaching are courageous acts. They involve journeying through unknown and unexplored terrain. The journey can he joyous and/or painful. Teaching and learning can evoke strong commitments to personal action. Both teachers and learners experience the complexity of the learning and teaching task. This grounded theory study sought to 'wonder' about the essence of teaching and learning; to investigate the relationship/s that teachers identified within teaching and learning, and to search for priorities, connections, similarities and differences. Melody, Kath, Nadine, Tori, Kerryn and Kaye were the six participants of the study who shared the beliefs and values they held as early childhood educators engaged in various teaching and learning contexts. They participated in interviews, created and discussed teaching and learning metaphors and joined together to take part in a focus group discussion. Emerging from the data were two theoretical metaphors that revealed relationships to be at the H.E.A.R.T. and R.O.O.T. of teaching and learning. The letters of each metaphor represented a category of inter-related properties inherent in teaching and learning relationships. As the project progressed, these two metaphors merged into one revealing relational connectedness within teaching and learning to be Holistic, Embedded, Authentic, Reciprocal and Transformational. Participants confirmed that the emergent metaphor H.E.A.R.T. had a strong sense of "fit, relevance and working" (Glaser, 1992, p. 15) in relation to their day-to-day teaching and learning experiences. Therefore, this thesis highlights the importance of relational connectivity in teaching and learning.
Keywords: Teacher-student relationships; Early childhood teachers; Teaching